Can green hydrogen exports contribute to regional economic development? Exploring scenarios from the Dutch-Brazilian green hydrogen corridor for the state of Ceará - Clara Rabelo Caiafa; Amaro Olimpio Pereira; Henny Romijn; Heleen de Coninck (Austrian Institute of Economic Research (WIFO), 2023)
To meet climate change mitigation targets, an exponential increase in global green hydrogen trade is expected. Countries rich in renewable energy resources would be in a favourable position to become exporters, potentially bringing opportunities for socio-economic development. The Brazilian state of Ceará is developing a large-scale green hydrogen hub, which is expected to provide one-fifth of European Union (EU) imports by 2030 via the green corridor between Ceará and The Netherlands. Located in what has historically been the least-developed Brazilian region, the green hydrogen hub could bring unique opportunities for regional development in Ceará. However, while empirical studies on economic impacts from other renewable energy projects in developing economies show limited localised benefits, the potential economic co-benefits from export-oriented green hydrogen projects remains uncertain. This study combines semi-structured interviews and input-output modelling to estimate impacts on value-added, income and jobs (by gender) in Ceará according to four local content share scenarios and three renewable energy technologies (onshore wind, offshore wind and solar photovoltaics). By doing so, this study is the first to estimate the potential for economic co-benefits from export-oriented green hydrogen projects in a developing economy context, in a sub-national level, while accounting for technology- and project-specificity as well as impacts on gender inequality. Results suggest that highly internationalized scenarios, that is, with low local content shares and dominated by multinational companies, would not only present local benefits that are often an order of magnitude lower, but could, through distributional implications of employment types, also exacerbate existing income and gender inequalities.
Keywords: O14; O19; Q56; R58; 330; Economic Co-benefits; Green Hydrogen; Gender; Input-Output Analysis; Regional development; Brazil